Three-Year Follow-Up of Participants from a Self-Weighing Randomized Controlled Trial - Lua Wilkinson; Carly R. Pacanowski; David Levitsky (Journal of Obesity)
Frequent self-weighing is associated with weight loss maintenance. Several years ago, we investigated frequent self-weighing’s effect on weight loss and found the participants lost a significant amount of weight. Three years after this trial's end, participants were contacted for an update on their weight and self-weighing frequency. Weight change and self-weighing frequency since the end of the study were assessed. We hypothesized that participants who maintained frequent self-weighing behavior would have maintained their weight loss. Out of 98 participants enrolled in the RCT, 37% (n = 36) participated in this follow-up study. Total weight loss during the trial for the follow-up participants was 12.7 ± 19.4 lbs (p<0.001). Three years after intervention, participants regained 0.9 ± 4.34 lbs, a value that was not statistically different from zero (p=0.75). This did not differ by gender (p=0.655). Over 75% of these participants continued to weigh themselves at least once a week. Frequent self-weighing may be an effective, low-cost strategy for weight loss maintenance. Future research should further investigate the role of self-weighing in long-term weight gain prevention.